Trickster Narratives of the New World: Erdrich, Dorris, Columbus - Madsen, Deborah Lea (Edwin Mellen Press (Lewiston), 2009)
The trickster figure, the shape-shifting, healing culture-hero Nanabozho, is central to Anishinaabe culture and the writings of contemporary writers of Anishinaabe descent, such as Louise Erdrich and Gerald Vizenor. In the introduction to Narrative Chance (1989), for example, Vizenor writes: "The trickster is a communal sign in a comic narrative; the comic holotrope (the whole figuration) is a consonance in tribal discourse. Silence and separation, not monologues in social science methodologies, are the antitheses of trickster discourse" (emphasis in original, 1989, 9). Others, like the Anishinaabe scholar Lawrence W. Gross, place the trickster directly at the heart of efforts to ensure tribal cultural survival. In this essay, I want to analyze the role of trickster discourses in response to the impact of colonization in Louise Erdrich's fiction, with a particular focus on the novel she co-authored with Michael Dorris, The Crown of Columbus (1991) and their subsequent writing for young adults, specifically the children's narratives dealing with the period of first contact with Europeans, such as Dorris's Morning Girl (1992), Guests (1995) and Sees Behind Trees (1996), as well as Erdrich's The Birchbark House (1999) and The Game of Silence (2005). These texts are quite different from the narratives published under Erdrich's name alone. For example, her close attention to tribal Anishinaabe histories, language, culture, and ritual are supplanted by a pan-Indian focus in the narratives that carry Dorris's name. To what extent, then, can we discover an Anishinaabe trickster aesthetic at work in these narratives? This is an important question because the structural weaknesses perceived by some reviewers in The Crown of Columbus have been rationalized by scholars like Susan Farrell who invoke the trickster figure to account for the narrative's distinctive style. Where Farrell deploys the trickster in a postmodern aesthetic context, I want to study the ways in which trickster discourses operate in the context of historical trauma. Nanabozho is a comic, healing force in Anishinaabe narratives; however, not all shape-shifting, deconstructive discourses are trickster discourses and these faux-tricksters may be available for conservative and destructive forms of appropriation that perpetuate the traumatic conditions of Native American experience.